Nomenclatural and taxonomic problems related to the electronic publication of new nomina and nomenclatural acts in zoology, with brief comments on optical discs and on the situation in botany - Dubois, Alain; Crochet, Pierre-André; Dickinson, Edward C.; Nemésio, André; Aescht, Erna; Bauer, Aaron M.; Blagoderov, Vladimir; Bour, Roger; de Carvalho, Marcelo R.; Desutter-Grandcolas, Laure; Frétey, Thierry; Jäger, Peter; et al. (Zootaxa, 2013)
In zoological nomenclature, to be potentially valid, nomenclatural novelties (i.e., new nomina and nomenclatural acts) need first to be made available, that is, published in works qualifying as publications as defined by the International Code of zoological Nomenclature (“the Code”). In September 2012, the Code was amended in order to allow the recognition of works electronically published online after 2011 as publications available for the purpose of zoological nomenclature, provided they meet several conditions, notably a preregistration of the work in ZooBank. Despite these new Rules, several of the long-discussed problems concerning the electronic publication of new nomina and nomenclatural acts have not been resolved. The publication of this amendment provides an opportunity to discuss some of these in detail. It is important to note that: (1) all works published only online before 2012 are nomenclaturally unavailable; (2) printed copies of the PDFs of works which do not have their own ISSN or ISBN, and which are not obtainable free of charge or by purchase, do not qualify as publications but must be seen as facsimiles of unavailable works and are unable to provide nomenclatural availability to any nomenclatural novelties they may contain; (3) prepublications online of later released online publications are unavailable, i.e., they do not advance the date of publication; (4) the publication dates of works for which online prepublications had been released are not those of these prepublications and it is critical that the real release date of such works appear on the actual final electronic publication, but this is not currently the case in electronic periodicals that distribute such online prepublications and which still indicate on their websites and PDFs the date of release of prepublication as that of publication of the work; (5) supplementary online materials and subsequent formal corrections of either paper or electronic publications distributed only online are nomenclaturally unavailable; (6) nomenclatural information provided on online websites that do not have a fixed content and format, with ISSN or ISBN, is unavailable. We give precise examples of many of these nomenclatural problems. Several of them, when they arise, are due to the fact that the availability of nomenclatural novelties now depends on information that will have to be sought not from the work itself but from extrinsic evidence. As shown by several examples discussed here, an electronic document can be modified while keeping the same DOI and publication date, which is not compatible with the requirements of zoological nomenclature. Therefore, another system of registration of electronic documents as permanent and inalterable will have to be devised. ZooBank also clearly needs to be improved in several respects. Mention in a work of its registration number (LSID) in ZooBank would seem to be possible only if this registration has occurred previously, but some works that have purportedly been registered in ZooBank are in fact missing on this web application. In conclusion, we offer recommendations to authors, referees, editors, publishers, libraries and the International Commission on Zoological Nomenclature, in the hope that such problems can be limited along with the potential chaos in zoological nomenclature that could result, if careful attention is not paid to the problems we highlight here, from a somewhat misplaced, and perhaps now widespread, understanding that electronic publication of nomenclatural novelties is now allowed and straightforward. We suggest that, as long as the problematic points linked to the new amendment and to electronic publication as a whole are not resolved, nomenclatural novelties continue to be published in paper-printed journals that have so far shown editorial competence regarding taxonomy and nomenclature, which is not the case of several recent electronic-only published journals.